ANALISIS LINGKUNGAN KERJA DALAM RANGKA MENINGKATKAN KINERJA PEGAWAI PADA KANTOR KELURAHAN GROGOL KECAMATAN LIMO KOTA DEPOK - Atfal Fadilah; Aden Prawiro Sudarso (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstract. This study aims to analyze the influence of the work environment on improving employee performance at the Grogol Urban Village Office, Limo District, Depok City. The work environment is a critical factor that can drive employee motivation, comfort, and productivity in carrying out their duties. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The findings show that several aspects of the work environment, such as workplace facilities, cleanliness, air circulation, and coworker relations, still need improvement. A supportive and comfortable work environment has been proven to enhance employee performance in terms of quality, quantity, responsibility, and attitude. Therefore, improving work environment conditions is a strategic step toward achieving optimal employee performance. Keywords: Work Environment, Employee Performance, Grogol Urban Village, Human Resources